Analysis of final student quarterlife crisis based on gender - Sheelvia Agusti; Ifdil Ifdil; Berru Amalianita (Konselor, 2022)
This study aims to analyze the quarterlife crisis level of final students of the Guidance and Counseling Department and to evaluate the difference in the level of quarterlife crisis of male and female final students of the Guidance and Counseling Department, Universitas Negeri Padang . This type of research is descriptive and comparative. The sample of this study was the final students of Guidance and Counseling including 37 male students and 163 female students. Data were analyzed using descriptive analysis and T-test with the help of JASP for windows version 16.4. The results of the study revealed that the quarterlife crisis of the final Guidance and Counseling students was in the moderate category, the quarterlife crisis of the female final Guidance and Counseling students was in the high category and there was a significant difference between the level of quarterlife crisis of the final male and female students of Guidance and Counseling.